Pengembangan Model Pembelajaran Drama Berbasis Kreativitas Di Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara - Diani Syahputri (EDUTECH, 2015)
The aims  of this study is to give the description the development model of learning drama based on creativity and how the students respond  toward teaching learning proses based on creativity. The sample of this research is the students of Teacher Trainning and education semester V      at Academic year  2014/2015 which contained 35 students. Descriptive quantitative and qualitatitive be designed. In this study can be developed four skills of languages such as; speaking, listening, reading and writing. The Instruments of the research are speaking test, listening test the students observed the students act as actors speaking, in reading test, the students read the text drama and writing test, the students write a simple drama.  Keywords: development, learning model, creativity, drama